Clinical manifestations, laboratory findings, treatment and outcome of acute organophosphate or carbamate intoxication in 39 cats. (18th April 2022) - Klainbart, Sigal; Grabarnik, Meital; Kelmer, Efrat; Chai, Orit; Cuneah, Olga; Segev, Gilad; Aroch, Itamar
Abstract: Background: Organophosphates and carbamates are important sources of intoxication for humans and animals. However, large‐scale studies of these intoxications in cats are unavailable. Methods: The medical records of 39 cats presented to a veterinary teaching hospital with acute organophosphate or carbamate intoxication were reviewed retrospectively. Results: Mortality in intoxicated cats was 15%. Low respiratory rate and low rectal temperature at presentation were associated with death. Other common clinical signs included weakness, ataxia, apathy, recumbency, anorexia and bradycardia, but these were unassociated with the outcome. The common biochemical abnormalities included decreased serum butyryl‐choline esterase activity, acidaemia, hypercarbaemia and total hypocalcaemia, and increased creatine kinase activity and total plasma protein concentration. There were no significant differences in haematological, biochemical and blood gas analytes between survivors and non‐survivors. Common medications and treatments included 2‐pyridine aldoxime methyl‐chloride‐pralidoxime (2‐PAM) (74%), metoclopramide (64%), antibiotics (64%), diphenhydramine (59%) and atropine sulphate (54%). There were no significant drug and treatment differences between survivors and non‐survivors. The secondary complications of the intoxication included pneumonia (10%), acute kidney injury (10%) and pancreatitis (8%). Conclusions: Acute cholinergic crisis due to organophosphate or carbamate intoxication has a fair prognosis in cats. Low respiratory rate and low rectal temperature at presentation were associated with death. The most commonly used specific medications in this study included 2‐PAM, diphenhydramine and atropine sulphate.